Insight into contact force local impedance technology for predicting effective pulmonary vein isolation - Lepillier, Antoine; Maggio, Ruggero; De Sanctis, Valerio; Malacrida, Maurizio; Stabile, Giuseppe; Zakine, Cyril; Champ-Rigot, Laure; Anselmino, Matteo; Segreti, Luca; Dell’Era, Gabriele; Garnier, Fabien; Mascia, Giuseppe; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background. Highly localized impedance (LI) measurements during atrial fibrillation (AF) ablation have the potential to act as a reliable predictor of the durability of the lesions created. Objective. We aimed to collect data on the procedural parameters affecting LI-guided ablation in a large multicenter registry. Methods. A total of 212 consecutive patients enrolled in the CHARISMA registry and undergoing their first pulmonary vein (PV) isolation for paroxysmal and persistent AF were included. Results. In all, 13,891 radiofrequency (RF) applications of ≥3 s duration were assessed. The first-pass PV isolation rate was 93.3%. A total of 80 PV gaps were detected. At successful ablation spots, baseline LI and absolute LI drop were larger than at PV gap spots (161.4±19Ω vs 153.0±13Ω, p<0.0001 for baseline LI; 22.1±9Ω vs 14.4±5Ω, p<0.0001 for LI drop). On the basis of Receiver operating characteristic curve analysis, the ideal LI drop, which predicted successful ablation, was >21Ω at anterior sites and >18Ω at posterior sites. There was a non-linear association between the magnitude of LI drop and contact-force (CF) (r=0.14, 95%CI: 0.13 to 0.16, p<0.0001) whereas both CF and LI drop were inversely related with delivery time (DT) (-0.22, -0.23 to -0.20, p<0.0001 for CF; -0.27, -0.29 to -0.26, p<0.0001 for LI drop). Conclusion. An LI drop >21Ω at anterior sites and >18Ω at posterior sites predicts successful ablation. A higher CF was associated with an increased likelihood of ideal LI drop. The combination of good CF and adequate LI drop allows a significant reduction in RF DT.